Sociocultural and economic factors influencing the use of HIV/AIDS information by Women in Ugep, Cross River State, Nigeria (2014)
The sociocultural and economic factors affecting the utilization of HIV/AIDS among women in Ugep, Yakurr Local Government Area, Cross River State were empirically investigated. Systematic sampling technique was used to administer four hundred copies of structured questionnaire to adults with a mean age of 25.5 years in the four traditional council wards that make up Ugep. Stepwise regression generated two predictive models. The second being the full model being significantly (p<0.01) explained 80.5% in the variability of HIV/AIDS information use (R2 = 0.805) with marital status and occupation identified as the most significant socioeconomic variables The study also identified male preference, taboo on contraceptive use and polygamy (polygyny) as predominant cultural practices that hindered women’s use of HIV/AIDS information for healthy sexual behaviour as they may not be able to negotiate for protected sexual intercourse from their husbands/partners. The study suggested that women should be empowered to participate effectively in family planning decision